Effect of Resin Cement at Different Thicknesses on the Fatigue Shear Bond Strength to Leucite Ceramic - Arcila, Laura Viviana Calvache [UNESP]; Gomes, Laís Carolina Landim [UNESP]; Ortiz, Laura Patricia Nadal [UNESP]; Costa, Mardoqueu M. Da; Tribst, João Paulo Mendes; Bottino, Marco Antonio [UNESP]; Saavedra, Guilherme De Siqueira Ferreira Anzaloni [UNESP]; De Melo, Renata Marques [UNESP] (Thieme, 2022)
Objectives This in vitro study was performed to evaluate fatigue survival by shear test in the union of leucite-reinforced feldspathic ceramic using different cement thicknesses. Materials and Methods Leucite-reinforced glass ceramics blocks were sectioned in 2-mm thick slices where resin cylinders were cemented. The samples were distributed in two experimental groups (n = 20) according to the cement thickness (60 and 300 μm). The specimens of each group were submitted to the stepwise fatigue test in the mechanical cycling machine under shear stress state, with a frequency of 2 Hz, a step-size of 0.16 bar, starting with a load of 31 N (1.0 bar) and a lifetime of 20,000 cycles at each load step. Results The samples were analyzed in a stereomicroscope and scanning electron microscopy to determine the failure type. There is no significant difference between the mean values of shear bond strength according to both groups. Log-rank (p = 0.925) and Wilcoxon (p = 0.520) tests revealed a similar survival probability in both cement layer thicknesses according to the confidence interval (95%). The fracture analysis showed that the mixed failure was the most common failure type in the 300-μm thickness group (80%), while adhesive failure was predominant in the 60-μm thickness group (67%). The different cement thicknesses did not influence the leucite ceramic bonding in fatigue shear testing; however, the thicker cement layer increased the predominance of the ceramic material failure. Conclusion The resin cement thicknesses bonded to leucite ceramic did not influence the long-term interfacial shear bond strength, although thicker cement layer increased the ceramic material cohesive failure. Regardless the cement layer thickness, the shear bond strength lifetime decreases under fatigue.
Keywords: cement; ceramic; failure load; fatigue; shear strength